2020
DOI: 10.9734/ajaees/2020/v38i830389
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Buying Behavior of Hybrid Paddy Seed Growers

Abstract: This study was on factors influencing buying behavior of the hybrid paddy seed growers among selected districts of Bihar with following objectives source and level of awareness, buying behavior of farmers and promotion of sales at retail level. The 155 farmers were selected from 27 blocks of six sample districts of Bihar state which includes Banka, Bhagalpur, Katihar, Munger, Purnea and Samastipur. Structured interview schedule was used for collection of data. The Ex-post facto research design was used in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Top consideration of dealers/ retailers for marketing the product of the company : Dealers/retailers play an important role in rural marketing for creating demand for hybrid paddy seeds among growers (Pandey et al, 2020). So, it is necessary to understand driving force of distributors and retailers for recommending a particular brand of product to the farmers.…”
Section: Methodsmentioning
confidence: 99%
“…Top consideration of dealers/ retailers for marketing the product of the company : Dealers/retailers play an important role in rural marketing for creating demand for hybrid paddy seeds among growers (Pandey et al, 2020). So, it is necessary to understand driving force of distributors and retailers for recommending a particular brand of product to the farmers.…”
Section: Methodsmentioning
confidence: 99%
“…Private sector is playing its part in engendering vigorous rivalry, which will ultimately benefit the farmers. Once the private sector is convinced that there is a demand for hybrid seed, the willingness to invest in commercial seed production as it is moderately profitable [1][2][3][4][5].…”
Section: Company Profilementioning
confidence: 99%
“…Ahmad (2018) reported that the topmost factors to which farmers give preference while buying hybrid seeds were yield potential, wilt resistance, brand image, timely availability and germination percentage of seed. Pandey [12] reported that majority of the farmers were aware of hybrid paddy seed dealers/retailers play an important role in rural marketing for creating demand among hybrid paddy seeds. Mustafiz [13] concluded that lack of market information, poor institutions and arrangements, poor marketing infrastructures, transportation system, and high and unfair profit margin distribution among the value chain actors with little share to the farmers in the vegetable seed market.…”
Section: Review Of Literaturementioning
confidence: 99%